A facile and one-step ethanol-thermal synthesis of MoS2 quantum dots for two-photon fluorescence imaging. Issue 1 (30th November 2015) - Gu, Wei; Yan, Yinghan; Cao, Xuni; Zhang, Cuiling; Ding, Caiping; Xian, Yuezhong
Abstract : MoS2 quantum dots with two-photon fluorescence features are synthesized through a one-step solvothermal approach and successfully used for cellular bioimaging. Abstract : Two-photon fluorescent (TPF) molybdenum disulfide quantum dots (MoS2 QDs) were synthesized through a facile and one-step solvothermal approach. The MoS2 QDs exhibit small size and high stability. Because of their low toxicity and TPF ability, the MoS2 QDs are successfully applied in two-photon fluorescence bio-imaging.